(untitled) (Delito y Sociedad, 2018)
The purpose of this paper is to provide a panoramic view of the formation of an Argentinian penitentiary knowledge from its origins until the middle of the 20th century. The 1850s are taken as a first divisory point since, with the sanction of the National Constitution and the inauguration of the Chair of Criminal Law at the University of Buenos Aires, began a process of legal normalization of a liberal criminal knowledge. The analysis concludes in 1946, given that, after the arrival of Peronism in power, the “Dirección General de Institutos Penales” promoted a series of substantial transformations that produced an inflection in penitentiary speeches and practices.